The recruitment of VET teachers and the failure of policy in England's further education sector. Issue 2 (17th February 2019) - Hanley, Pam; Orr, Kevin
ABSTRACT: England's further education (FE) sector has been characterised by instability and policy churn for at least three decades during which time reform of vocational education and training (VET) has been piled on top of reform, with few resulting in lasting change. In the context of another ambitious new reform of VET in England, this article reports on a study that examined the chronic difficulties in recruiting teachers of vocational science, engineering and technology (SET) to FE colleges. We argue that these difficulties in recruiting SET teachers reveal persistent weaknesses in policy planning for the English VET sector and help to explain the serial failure of VET policy in England.